The impact of cash holding on stock returns during a crisis： evidence from Chinese firms in COVID-19 - CHEN, LEYAN (2022)
This paper uses an event study approach and data from the SSE A-share Main Board and SZSE A-share to explore whether cash holdings could mitigate the negative influence of COVID-19 on share prices. In this paper, the outbreak was found to have a negative effect on the share price. Within the event window, large companies with more cash and less debt were less affected by the epidemic. Moreover, the positive impact of cash holding on stock prices was found to be more significant in companies with low cash holdings, while excessive cash holdings could not contribute to stock prices. Further analysis of which factors would affect the relationship. Firstly, agency issues still negatively affect the relationship between the two. Second, the positive influence of cash holding on share price is more noticeable among firms with higher information transparency. Third, in a regression grouped by equity, the positive impact of cash holding on share prices is more significant among non-state-owned firms. Based on three theories of cash holdings, this paper examines whether cash holdings could inhibit a firm's share price decline under an epidemic. The trade-off theory has been confirmed. And it is suggested that cash has a precautionary value and the relationship between cash holding and the firm’s value would be an inverted U-shaped relationship.